2023
DOI: 10.1038/s41598-023-36296-w
|View full text |Cite
|
Sign up to set email alerts
|

Placebo effects on nausea and motion sickness are resistant to experimentally-induced stress

Abstract: Nausea often occurs in stressful situations, such as chemotherapy or surgery. Clinically relevant placebo effects in nausea have been demonstrated, but it remains unclear whether stress has an impact on these effects. The aim of this experimental study was to investigate the interplay between acute stress and placebo effects in nausea. 80 healthy female volunteers susceptible to motion sickness were randomly assigned to either the Maastricht Acute Stress Test or a non-stress control condition, and to either pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
1
0
0
Order By: Relevance
“…This study revealed that buckling a seat belt while travelling, in addition to protecting against an accident and being thrown out of the seat, helped to reduce feelings of illness. The findings coincided with earlier research conducted in various locations [ 11 , 32 , 33 ]. All of the mentioned above studies showed the importance of seat belt use only in terms of accident and injury prevention.…”
Section: Resultssupporting
confidence: 92%
“…This study revealed that buckling a seat belt while travelling, in addition to protecting against an accident and being thrown out of the seat, helped to reduce feelings of illness. The findings coincided with earlier research conducted in various locations [ 11 , 32 , 33 ]. All of the mentioned above studies showed the importance of seat belt use only in terms of accident and injury prevention.…”
Section: Resultssupporting
confidence: 92%